Inter-relationships among potato traits and their significance in determining tuber yield (Makerere University Journal of Agricultural & Environmental Sciences, 2003)
Research aimed at selecting potato varieties from Standard International Field Trials (SIFT) with high tuber was carried out at five locations during three seasons of 2001 - 2002 in Uganda. Data were collected on number of leaves, number of stems, plant height, percentage tuber dry matter, number of tubers, mean tuber weight and yield. Results from the simple phenotypic correlation and multiple regressions indicated that mean tuber weight (r = 0.61, P
Keywords: Multiple Regression; path coefficient analysis; phenotypic correlation; Solanum tuberosum; yield; Uganda